PENGARUH PENERAPAN TEKNIK PEMODELAN BERBANTUAN MEDIA GAMBAR TERHADAP KETERAMPILAN MENULIS KARANGAN DESKRIPSI SISWA KELAS X SMK PEMBINA BANGSA BUKITTINGGI - Rintina, Nila Malda; Arief, Ermawati; Noveria, Ena (Universitas Negeri Padang, 2016)
ABSTRACTÂ This research aims to describe the influence techniques modeling assist media picture the skills of essay writing description class X SMK Pembina Bangsa Bukittinggi. The type of this research is quantitative research done using experimental design. The results of this research are three: (1) essay writing skills descriptionwhitout using modeling assist media picture of class X SMKPembina Bangsa Bukittinggi are in qualifying Nearly Enough (HC) with an average value of 51,30, (2) essay writing skills descriptionwith using modeling assist media picture of class X SMK Pembina Bangsa Bukittinggi are in qualification Good (B) with an average value of 78,15, and (3) descriptionessay writing skills class X SMKPembina Bangsa Bukittinggi of techniques modeling assist media picture.Â Kata Kunci: pengaruh, teknik pemodelan,media gambar,karangan deskripsi